Analyzing ICT Literacy and Determining Factors among Elementary School Students in Palembang - Chery Putri Claudia NR Claudia; Ribi Tri Aini Ribi; Ades Dwi Putri Ades; Nabila Raisyah Zahra Nabila (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
This study was conducted with the aim of describing the level of ICT (Information and Communication Technology) literacy of students at SD Negeri 95 Palembang and analyzing various relevant determining factors. A descriptive qualitative approach was used in this research, involving 21 fourth-grade students and one homeroom teacher as the main subjects. Data were collected through questionnaires, interviews, observations, and documentation, and then analyzed using the Miles & Huberman model. The findings reveal that although all students have mastered basic digital device skills, the level of technology use in the context of academic learning tends to be minimal. Data indicate that less than one-third (28.5%) of students use computers/tablets to complete school assignments, and just over half (52.3%) have an understanding of online learning applications. Four main variables affecting ICT literacy were identified, namely accessibility of facilities, competence Teachers, family support (parents), and student learning motivation. ICT literacy improvement will be more effective if supported by adequate facilities, skilled teachers, and family involvement